Abnormal cortical functional activity in patients with ischemic white matter lesions: A resting-state functional magnetic resonance imaging study. (22nd March 2017) - Ding, Xin; Ding, Jurong; Hua, Bo; Xiong, Xingzhong; Xiao, Li; Peng, Fang; Chen, Lin; Pan, Xianfang; Wang, Qingsong
Highlights: We examine the relationship between WMLs and cognitive function using a ReHo method. Abnormal regions are related to memory, attention and executive and motor function. Altered regions in the DMN, FPCN and motor area correlate with cognitive test scores. The findings improve our understanding of pathophysiological mechanisms of WMLs. Abstract: There is increasing evidence that white matter lesions (WMLs) are associated with cognitive impairments. The purpose of this study was to explore the relationship of WMLs with cognitive impairments from the aspect of cortical functional activity. Briefly, Sixteen patients with ischemic WMLs and 13 controls participated in this study. A regional homogeneity (ReHo) approach was used to investigate altered neural coherence in patients with ischemic WMLs during the resting state. A correlation analysis was further performed between regions with altered ReHo and cognitive test scores, including Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA), in the patient group. Finally, we found regions with altered ReHo values in patients with ischemic WMLs to be involved in default mode network (DMN), frontal-parietal control network (FPCN), dorsal attention network (DAN), motor network and right temporal cortex. Moreover, some altered regions belonging to DMN, FPCN and motor network were significantly correlated with cognitive test scores. Our results provide neuroimaging evidence for the impairments of memory, attention, executive and motor function in patients with ischemic WMLs. It is interesting to note that the decreased ReHo was mainly in the anterior brain regions, while increased ReHo in the posterior brain regions, which may indicate a failure down regulation of spontaneous activity in posterior regions. In summary, this study indicates an important role of specific cortical dysfunction in cognitive associated with WMLs.